Chanakya’s Foreign Policy: Relevance of Chanakya's Ancient Foreign Policy in Modern Times (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Kautilya’s Arthashastra which means ‘science of wealth creation’ is a work by genius of ancient Indian economy, the author identified as Kautilya or Chanakya is a well known historical figure who shaped the future of India during the Magadhan times. Chanakya’s speaks about various forms of quality governance, public finance, corporate governance, governance models foreign policy etc. These foreign policies are explained with appropriate examples using his six aspects.Almost he has written about foreign policy 2000 years ago but still it is very useful for today’s conditions.